Fotocatálises e metodologias sintéticas via formação de complexos Doador-Aceptor de Elétrons (EDA) - Villela, Lucas Facuri (Universidade Federal de São Carlos, 2021)
Chemical transformations promoted by the irradiation of light have aroused the interest of the synthetic community since the beginning of the 20th century. However, due to the lack of appropriate technologies to perform photoinduced transformations, photochemistry and photocatalysis remained in the perception of many chemists as a specialized technique, with few practical applications and on large scale. Currently, with the development of new photochemical methods and the emergence of new technologies that have facilitated access to different sources of irradiation, the interest in investing in photochemical transformations has reappeared in search of more efficient methodologies that employ milder conditions. Thus, in recent years as an alternative to the commonly used photocatalytic methods, organic reactions induced by visible light via the formation of EDA complexes have received great attention due to their synthetic potential to promote a wide variety of chemical transformations involving the formation of carbon-carbon and carbon-heteroatom bonds.
Photocatalysis and synthetic methodologies via formation of electron donor-acceptor complexes (EDA)
Keywords: Fotoquímica; Fotocatálise; Luz visível; complexos EDA; Photochemistry; Photocatalysis; visible light; EDA complexes; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FOTOQUIMICA ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA